2017
DOI: 10.48550/arxiv.1706.07126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cycle class map from Chow groups with modulus to relative $K$-theory

Abstract: Let X be a smooth quasi-projective d-dimensional variety over a field k and let D be an effective, non-reduced, Cartier divisor on it such that its support is strict normal crossing. In this note, we construct cycle class maps from (a variant of) the higher Chow group with modulus of the pair (X; D) in the range (d + n, n) to the relative K-groups Kn(X; D) for every n ≥ 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…W. Kai [29] established a moving lemma for cycle complexes with modulus which implies an appropriate contravariant functoriality of the Nisnevich version of (1.3) (see Theorem 2.12 for the precise statement). A work by R. Iwasa and W. Kai [27] provides Chern classes from the relative K-groups of the pair (X, D) to the Nisnevich motivic cohomology groups H * M,Nis (X|D, Z( * )), while a construction of F. Binda [3,Theorem 4.4.10] (see also [4]) gives cycle classes from the groups of higher 0-cycles with modulus CH d+n (X|D, n) to the relative K-groups K n (X, D). Other positive results are obtained in [32], [43] and [5].…”
mentioning
confidence: 99%
“…W. Kai [29] established a moving lemma for cycle complexes with modulus which implies an appropriate contravariant functoriality of the Nisnevich version of (1.3) (see Theorem 2.12 for the precise statement). A work by R. Iwasa and W. Kai [27] provides Chern classes from the relative K-groups of the pair (X, D) to the Nisnevich motivic cohomology groups H * M,Nis (X|D, Z( * )), while a construction of F. Binda [3,Theorem 4.4.10] (see also [4]) gives cycle classes from the groups of higher 0-cycles with modulus CH d+n (X|D, n) to the relative K-groups K n (X, D). Other positive results are obtained in [32], [43] and [5].…”
mentioning
confidence: 99%
“…A cycle class map of the kind given in Corollary 7.23 was constructed in [1]. In that construction, Binda uses a different definition for the Chow groups with modulus compared to the ones described in § 2.5.…”
Section: Chow Group With Modulus and Relative Motivic Cohomologymentioning
confidence: 99%
“…They have also shown that the cycle class map is injective if X is affine and the base filed is algebraically closed. Also, Binda [Bi18] constructed a cycle class map for higher zero cycles with modulus using a slightly different (stronger) modulus condition.…”
mentioning
confidence: 99%